Islamic perspectives on the principles of biomedical ethics Muslim religious scholars and biomedical scientists in face-to-face dialogue with western bioethicists - Ghaly, Mohammed (Intercultural dialogue in bioethics, 2016)
Islamic Perspectives on the Principles of Biomedical Ethics presents results from a pioneering seminar in 2013 between Muslim religious scholars, biomedical scientists, and Western bioethicists at the research Center for Islamic Legislation & Ethics, Qatar Faculty of Islamic Studies. By examining principle-based bioethics, the contributors to this volume addressed a number of key issues related to the future of the field. Discussion is based around the role of religion in bioethical reasoning, specifically from an Islamic perspective. Also considered is a presentation of the concept of universal principles for bioethics, with a response looking at the possibility (or not) of involving religion. Finally, there is in-depth analysis of how far specific disciplines within the Islamic tradition -- such as the higher objectives of Sharia (maqāṣid al-Sharī'ah) and legal maxims (qawā'id fiqhīyah) -- can enrich principle-based bioethics.